2015
DOI: 10.3109/14767058.2015.1070140
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia in twin pregnancies: association with selective intrauterine growth restriction

Abstract: sIUGR is associated with increased odds of developing severe PE in twin pregnancies, leading to poorer perinatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…In the human condition, preeclampsia, soluble anti-angiogenic factors have been measured in the maternal circulation 27 . These findings support a theory that interference with fetal angiogenesis may contribute to infant disease and growth restriction 28 29 . We probed into whether UPI increased maternal soluble Flt-1 (sFlt-1) that would bind VEGF and thereby reduce circulating VEGF.…”
Section: Resultssupporting
confidence: 84%
“…In the human condition, preeclampsia, soluble anti-angiogenic factors have been measured in the maternal circulation 27 . These findings support a theory that interference with fetal angiogenesis may contribute to infant disease and growth restriction 28 29 . We probed into whether UPI increased maternal soluble Flt-1 (sFlt-1) that would bind VEGF and thereby reduce circulating VEGF.…”
Section: Resultssupporting
confidence: 84%
“…The association between fetal growth disorders and the development of hypertension in twin pregnancies has been investigated, with evidence of conflicting results [ 8 , 9 , 10 , 11 , 12 , 13 ]. In small retrospective studies, the association between SGA and preeclampsia was not detected.…”
Section: Discussionmentioning
confidence: 99%
“…This was primarily because authors used singleton-based birthweight reference charts to define SGA, leading to a very high rate of SGA twins in both normotensive and hypertensive twin pregnancies [ 10 , 11 ]. Conversely, SGA was associated with an increased risk of preeclampsia in studies where a twin-specific birthweight chart was used [ 8 , 12 , 13 ]. In our study, SGA and FGR were associated with HDP using either singleton or twin charts; however, these associations were stronger when twin-specific charts were used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a retrospective cohort study from Chinese twin pregnancies revealed that PE occurred more frequently in selective IUGR (sIUGR) pregnancies than in normal growth twin pregnancies, and sIUGR was associated with increased odds of developing severe PE in twin pregnancies [25] . These 2 studies and ours were coming from different perspectives to look into the correlations between PE and IUGR in twin pregnancies.…”
Section: Discussionmentioning
confidence: 79%